SECTORAL CONTRIBUTION AND THEIR RELEVANCE IN INDIA: WITH SPECIAL REFERENCE TO THREE SOUTH INDIAN STATES - Sivasubramaniyan, K. (International Journal of Research -GRANTHAALAYAH, 2017)
Majority of the countries in the world has been functioning with its involvement in one or more of the three sectors of the economy such as agriculture, industry and services. In India, a large proportion of population live in poverty due to low level of skill development who are unable to cope with the available employment opportunities in the three sectors of the economy. Proper skill training not only benefits the work force and allows it to earn a decent living, but also contributes to the national economy by enhancing better productivity through the work force. Although India is an agricultural country, its importance in terms of giving employment and to generate adequate income to the people engaged in the sector has been gradually and steadily declining overtime. Consequently, industry and service sectors have been absorbing the displaced agricultural population to some extent. To what extent all the three sectors help the people to get employment and earn income for their livelihood in India, especially in the four southern states of India is discussed in the paper.